Privacy Enhancing Technologies 10th International Symposium, PETS 2010, Berlin, Germany, July 21-23, 2010. Proceedings - Atallah, Mikhail J.; Hopper, Nicholas J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 10th International Symposium, PETS 2010, held in Berlin, Germany in July 2010. The 16 revised full papers were carefully reviewed and selected from 57 submissions for inclusion in the book. The papers handle topics such as access control, privacy of web based search, anonymus webs of trust, security attacks, active timing attacks in lo-latency anonymus communication, network topology and web search with malicious adversaries.
Privacy Enhancing Technologies Symposium -- How Unique Is Your Web Browser? -- On the Privacy of Web Search Based on Query Obfuscation: A Case Study of TrackMeNot -- Private Information Disclosure from Web Searches -- Collaborative, Privacy-Preserving Data Aggregation at Scale -- Privacy-Preserving Queries over Relational Databases -- Achieving Efficient Query Privacy for Location Based Services -- Making a Nymbler Nymble Using VERBS -- Anonymous Webs of Trust -- Taming Big Brother Ambitions: More Privacy for Secret Handshakes -- Preventing Active Timing Attacks in Low-Latency Anonymous Communication -- Impact of Network Topology on Anonymity and Overhead in Low-Latency Anonymity Networks -- : An Architecture for Anonymous Low-Volume Communications -- Private Web Search with Malicious Adversaries -- unFriendly: Multi-party Privacy Risks in Social Networks -- The Impact of Unlinkability on Adversarial Community Detection: Effects and Countermeasures -- How to Share Your Favourite Search Results while Preserving Privacy and Quality.
Keywords: Computer science; Computer communication systems; Computer security; Data encryption (Computer science).; Computers; Algorithms; Computers and civilization; Computer Science; Computer Communication Networks; Theory of Computation; Systems and Data Security; Data Encryption; Algorithm Analysis and Problem Complexity; Computers and Society; Electronic books